2002
DOI: 10.1103/physrevb.66.064431
|View full text |Cite
|
Sign up to set email alerts
|

Extended droplet theory for aging in short-range spin glasses and a numerical examination

Abstract: We analyze isothermal aging of a four dimensional Edwards-Anderson model in detail by Monte Carlo simulations. We analyze the data in the view of an extended version of the droplet theory proposed recently (cond-mat/0202110) which is based on the original droplet theory plus conjectures on the anomalously soft droplets in the presence of domain walls. We found that the scaling laws including some fundamental predictions of the original droplet theory explain well our results. The results of our simulation stro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 67 publications
(220 reference statements)
4
73
0
Order By: Relevance
“…In fact, the growth of the dynamical correlation length at the critical point of different three-and fourdimensional spin glasses has been intensively investigated in the recent past. We mention here the Ising spin glass with a Bimodal 29,30 or a Gaussian 21,30 distribution of the couplings, the gauge glass with a Gaussian distribution 21 , the XY spin glass with a Bimodal distribution 31 Heisenberg spin glass with a Gaussian distribution 32 . All these studies reveal that for times t ≥ 20 the increase of the dynamical correlation length in various spin glasses (including some of the cases we consider in this work) is given by the simple power-law (26).…”
Section: Dimensionmentioning
confidence: 99%
“…In fact, the growth of the dynamical correlation length at the critical point of different three-and fourdimensional spin glasses has been intensively investigated in the recent past. We mention here the Ising spin glass with a Bimodal 29,30 or a Gaussian 21,30 distribution of the couplings, the gauge glass with a Gaussian distribution 21 , the XY spin glass with a Bimodal distribution 31 Heisenberg spin glass with a Gaussian distribution 32 . All these studies reveal that for times t ≥ 20 the increase of the dynamical correlation length in various spin glasses (including some of the cases we consider in this work) is given by the simple power-law (26).…”
Section: Dimensionmentioning
confidence: 99%
“…This conjecture was supported both by numerical simulation [3] and analytic work [4] (see, however, also ref. [5]). …”
mentioning
confidence: 99%
“…In [17] it is shown that quantum fluctuations in quantum glassy systems depress the phase transition temperature, in a glassy phase the aging effect survives the quantum fluctuations, and because of quantum fluctuations, the fluctuation-dissipation theorem is modified. In reference [19][20][21] it is shown that all terms in the dynamical equations governing the timeevolution of spin response and correlation function which are due to quantum effects, are irrelevant at long times. Quantum effects enter only through the renormalization of parameters in dynamical equations [19][20][21].…”
Section:  mentioning
confidence: 99%
“…is described by this model hamiltonian [4,13,20]. It is supposed that this model may also represent, for example, the physics of deuteron glass such as…”
Section: Model Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation